GA3 application in grapes (Vitis vinifera L.) modulates different sets of genes at cluster emergence, full bloom, and berry stage as revealed by RNA sequence-based transcriptome analysis - Upadhyay, Anuradha; Maske, Smita; Jogaiah, Satisha; Kadoo, Narendra Y.; Gupta, Vidya S. (Functional & Integrative Genomics, 2018)
In grapes (Vitis vinifera L.), exogenous gibberellic acid (GA3) is applied at different stages of bunch development to achieve desirable bunch shape and berry size in seedless grapes used for table purpose. RNA sequence-based transcriptome analysis was used to understand the mechanism of GA3 action at cluster emergence, full bloom, and berry stage in table grape variety Thompson Seedless. At cluster emergence, rachis samples were collected at 6 and 24 h after application of GA3, whereas flower clusters and berry samples were collected at 6, 24, and 48 h after application at full bloom and 3–4 mm berry stages. Seven hundred thirty-three genes were differentially expressed in GA3-treated samples. At rachis and flower cluster stage respectively, 126 and 264 genes were found to be significantly differentially expressed within 6 h of GA3 application. The number of DEG reduced considerably at 24 h. However, at berry stage, major changes occurred even at 24 h and a number of DEGs at 6 and 24 h were 174 and 191, respectively. As compared to upregulated genes, larger numbers of genes were downregulated. Stage-specific response to the GA3 application was observed as evident from the unique set of DEGs at each stage and only a few common genes among three stages. Among the DEGs, 67 were transcription factors. Functional categorization and enrichment analysis revealed that several transcripts involved in sucrose and hexose metabolism, hormone and secondary metabolism, and abiotic and biotic stimuli were enriched in response to application of GA3. A high correlation was recorded for real-time PCR and transcriptome data for selected DEGs, thus indicating the robustness of transcriptome data obtained in this study for understanding the GA3 response at different stages of berry development in grape. Chromosomal localization of DEGs and identification of polymorphic microsatellite markers in selected genes have potential for their use in breeding for varieties with improved bunch architecture.
Keywords: Bunch architecture; GA3 response; Microsatellite markers; RNA seq; Transcription factors; Vitis vinifera

Global transcriptome analysis of grapevine ( Vitis vinifera L.) leaves under salt stress reveals differential response at early and late stages of stress in table grape cv. Thompson Seedless - Upadhyay, Anuradha; Gaonkar, Tulsi; Upadhyay, Ajay Kumar; Jogaiah, Satisha; Shinde, Manisha P.; Kadoo, Narendra; Gupta, Vidya Shrikant (Plant Physiology and Biochemistry, 2018)
Among the different abiotic stresses, salt stress has a significant effect on the growth and yield of grapevine (Vitis vinifera L.). In this study, we employed RNA sequence based transcriptome analysis to study salinity stress response in grape variety Thompson Seedless. Salt stress adversely affected the growth related and physiological parameters and the effect on physiological parameters was significant within 10 days of stress imposition. A total of 343 genes were differentially expressed in response to salt stress. Among the differentially expressed genes (DEGs) only 42 genes were common at early and late stages of stress. The gene enrichment analysis revealed that GO terms related to transcription factors were over-represented. Among the DEGs, 52 were transcription factors belonging to WRKY, EREB, MYB, NAC and bHLH families. Salt stress significantly affected several pathways like metabolic pathways, biosynthesis of secondary metabolites, membrane transport development related pathways etc. 343 DEGs were distributed on all the 19 chromosomes, however clustered regions of DEGs were present on chromosomes 2, 5, 6 and 12 suggesting probable QTLs for imparting tolerance to salt and other abiotic stresses. Real-time PCR of selected genes in control and treated samples of grafted and own root vines demonstrated that rootstock influenced expression of salt stress responsive genes. Microsatellite regions were identified in ten selected salt responsive genes and highly polymorphic markers were identified using fifteen grape genotypes. This information will be useful for the identification of key genes involved in salt stress tolerance in grape. The identified DEGs could also be useful for genome wide analysis for the identification of polymorphic markers for their subsequent use in molecular breeding for developing salt tolerant grape genotypes.

Global study of MFS superfamily transporters in arabidopsis and grapes reveals their functional diversity in plants - Patil, Sucheta S.; Prashant, Ramya; Kadoo, Narendra Y.; Upadhyay, Anuradha; Gupta, Vidya S. (Plant Gene, 2019)
The Major Facilitator Superfamily (MFS) is the largest superfamily of secondary transporters present in all organisms, from prokaryotes to higher eukaryotes, that facilitates transport of diverse molecules like sugars, vitamins, amino-acids, hormones, etc. across cell membranes. The superfamily was further expanded to MFS Superfamily (MFSS) to integrate MFS with nine more families. The present study revealed their land plant specific diversity through identification across six species from unicellular alga to higher flowering plants. We identified 71, 131, 254, 260, 213 and 203 MFSS transporters in Chlamydomonas reinhardtii, Physcomitrella patens, Selaginella moellendorffii, Oryza sativa (var. Japonica), Arabidopsis thaliana and Vitis vinifera, respectively and classified them into MFSS families and subfamilies based on their transporter classification identifiers (TCIDs). Detailed analysis of 20 land plant specific subfamilies was conducted in A. thaliana and V. vinifera. Phylogenetic and gene duplication studies revealed the expansion of sugar porter and proton dependent oligopeptide transporter families in Arabidopsis and grape. The subcellular localization of the majority of the transporters was predicted to be in the plasma membrane. Furthermore, the microarray expression analysis of MFSS transporters from Arabidopsis and grapes revealed their multi-tissue-specificity and differential regulation under biotic and abiotic stress conditions. Studies of the transmembrane topology highlighted the presence of central cytoplasmic loop along with family specific topological variations that were evident from phylogenetic analysis. Overall, this study adds to the knowledge of functional and structural diversity and evolution of MFSS transporters in plants and opens the scope for detailed physiological and functional studies on these proteins.

Whole proteome analysis of GA(3) response at panicle stage in Grape (Vitis vinifera) CV. Thompson seedless - Maske, Smita; Upadhyay, Anuradha; Jogaiha, Satisha; Patil, Sucheta S.; Kadoo, Narendra Y.; Gupta, Vidya S. (Journal of Plant Growth Regulation, 2019)
Rachis elongation is a crucial process in producing good quality table grapes. In compact clustered grape variety like Thompson Seedless, treating the flower panicles with a mild dose of GA(3) results in loose clusters. We sprayed GA(3) on Thompson Seedless panicles immediately after emergence, and the samples were collected at 6 h and 24 h after application. Whole proteome analysis revealed significant differential expression of 530 proteins of the total 1288 expressed proteins at two time-points. GO term enrichment analysis revealed enrichment of GO terms related to translation, biosynthetic processes, and photosynthesis in GA(3)-treated samples. As the process of rachis elongation requires enhanced carbon metabolism and accumulation of sugars through the expansion of phloem area, we attribute this to the overexpression of several proteins involved in these processes. Significantly highly expressed proteins also belonged to biological processes like the generation of precursor metabolites, cellular protein metabolic processes, response to abiotic stimulus, and protein metabolic processes. This study might be the first of its kind in deciphering the contribution of a different group of proteins during rachis elongation as an early response to GA(3) application in seedless grapes. These results provide quality information on various physiological and biochemical changes occurring during early stages of rachis elongation.
Keywords: Bunch architecture; Gibberellic acid; Proteome; Rachis elongation; Vitis vinifera

Comparative proteomics unravels the differences in salt stress response of own-rooted and 110R-grafted thompson seedless grapevines - Patil, Sucheta; Shinde, Manisha; Prashant, Ramya; Kadoo, Narendra; Upadhyay, Anuradha; Gupta, Vidya (Journal of Proteome Research, 2020)
Thompson Seedless, a commonly grown table grape variety, is sensitive to salinity when grown on its own roots, and therefore, it is frequently grafted onto salinity-tolerant wild grapevine rootstocks. Rising soil salinity is a growing concern in irrigated agricultural systems. The accumulation of salts near the root zone severely hampers plant growth, leading to a decrease in the productive lifespan of grapevine and causing heavy yield losses to the farmer. In the present study, we investigated the differences in response to salinity between own-rooted Thompson Seedless (TSOR) and 110R-grafted Thompson Seedless (TS110R) grapevines, wherein 110R is reported to be a salt-tolerant rootstock. The grapevines were subjected to salt stress by treating them with a 150 mM NaCl solution. The stress-induced changes in protein abundance were investigated using a label-free shotgun proteomics approach at three time points viz. 6 h, 48 h, and 7 days of salt treatment. A total of 2793 proteins were identified, of which 246 were differentially abundant at various time-points in TSOR and TS110R vines. The abundance of proteins involved in several biological processes such as photosynthesis, amino acid metabolism, translation, chlorophyll biosynthesis, and generation of precursor metabolites was significantly affected by salt stress in both the vines but at different stages of stress. The results revealed that TSOR vines responded fervently to salt stress, while TS110R vines adopted a preventive approach. The findings of this study add to the knowledge of salinity response in woody and grafted plants and hence open the scope for further studies on salt stress-specific differences induced by grafting.
Keywords: 110R rootstock; gene ontology; grafting; label-free proteomics; salt stress; Vitis vinifera

Gibberellic acid induces unique molecular responses in ‘thompson seedless’ grapes as revealed by non-targeted metabolomics - Jadhav, Uma; Mundhe, Swapnil; Kumar, Yashwant; Jogaiah, Satisha; Upadhyay, Anuradha; Gupta, Vidya S.; Kadoo, Narendra Y. (Journal of Plant Growth Regulation, 2021)
Compact clusters and small berry size are the major problems associated with the commercialization of table grapes. The application of gibberellic acid 3 (GA3) has been a long-followed practice to overcome these issues. To analyze the molecular response of ‘Thompson Seedless’ grapes to GA3 treatment, we investigated the metabolomes of its rachises, clusters, and berries, 6 h and 24 h after the treatment. Metabolite profiling using non-targeted metabolomics approach revealed several metabolites, including arginine, proline, tyrosine, kaempferol, resveratrol, catechin, and so on as possible biomarkers of GA3 treatment in grapes. GA3 treatment greatly impacted the alanine, aspartate, and glutamate metabolism pathways, and the GA3-mediated alterations in the levels of certain plant growth regulators and primary metabolites were in accordance with important growth and developmental processes in grapes. This study highlights the effect of GA3 on the profiles of certain polyphenols impacting the flavone and flavonol biosynthesis pathways and hence the nutritional aspect of grapes. The results of this study would be useful to develop self-elongating varieties simplifying the grape cultivation.

Gibberellic acid induces unique molecular responses in `thompson seedless' grapes as revealed by non-targeted metabolomics - Jadhav, Uma; Mundhe, Swapnil; Kumar, Yashwant; Jogaiah, Satisha; Upadhyay, Anuradha; Gupta, Vidya S.; Kadoo, Narendra Y. (Journal of Plant Growth Regulation, 2021)
Compact clusters and small berry size are the major problems associated with the commercialization of table grapes. The application of gibberellic acid 3 (GA(3)) has been a long-followed practice to overcome these issues. To analyze the molecular response of `Thompson Seedless' grapes to GA(3) treatment, we investigated the metabolomes of its rachises, clusters, and berries, 6 h and 24 h after the treatment. Metabolite profiling using non-targeted metabolomics approach revealed several metabolites, including arginine, proline, tyrosine, kaempferol, resveratrol, catechin, and so on as possible biomarkers of GA(3) treatment in grapes. GA(3) treatment greatly impacted the alanine, aspartate, and glutamate metabolism pathways, and the GA(3)-mediated alterations in the levels of certain plant growth regulators and primary metabolites were in accordance with important growth and developmental processes in grapes. This study highlights the effect of GA(3) on the profiles of certain polyphenols impacting the flavone and flavonol biosynthesis pathways and hence the nutritional aspect of grapes. The results of this study would be useful to develop self-elongating varieties simplifying the grape cultivation.
Keywords: Biosynthetic pathways; GA(3) response; GA(3) signaling; Sultana grapes; Untargeted metabolomics